IMPLEMENTASI BALANCED SCORECARD SEBAGAI ALAT PENTERJEMAH STRATEGI DAN PENGUKURAN KINERJA PERUSAHAAN - Purnawiranti, Yuliana; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out and to analyze implementation of balanced scorecard as a tool forstrategic translator and performance assessment of company. The research method has been done by usingqualitative method, because this research is not meant to prove a hypothesis but it is meant to explore facts andconditions which occur during the research. Based on the research result it has been found, the presence of thebalanced scorecard method which is reviewed from a financial perspectives has shown the good result of financialperformance since profit increases every year, it can be reviewed from customer perspectives can be stated quitegood because the taste of Japanese food has become one of the most popular culinary which are favored by thesociety, when it is reviewed from the internal business process perspective in which the presence of innovationand operation has shown the performance of the company is excellent becausethe company always makesinnovation every year by introducing a new menu, when it is reviewed from the growth and learning perspectiveshows the condition of the performance of the company is quite good because can enhance the quality of theemployees. Based on the result of the research, it can be concluded that the balanced scorecard can provide clearperformance assessment, measurable, well-planned and coherent in realizing the vision, the mission and the goalas well as the companyâs strategy so some improvements can be done. In order to make the balanced scorecardmethod can be implemented properly on the company, a commitment from the top management and theunderlying management and the drafting teamis formedin translating theperformance assessment system isrequired.Keywords: System of Performance Measurement, Strategy Implementation, Perspective of Balanced Scorecard